ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH (Studi Empiris pada Bank Umum Syariah di Indonesia pada Periode 2014Q1 – 2018Q4) - Nur, Tegar Ochta; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2019)
The purpose of this study was to determine the effect of CAR, BOPO, NPF and FDR on the profitability of Islamic Commercial Bank in Indonesia.. Profitability is proxied by ROA.The sample in this study is Islamic commercial bank in Indonesia during the period 2013-2017. The number of samples were 11 banks taken by purposive sampling method. The analytical method of this study uses multiple linear regression with the SPSS 23 program which has previously passed the classic assumption test.The results of this study indicate that CAR has a positive and significant effect on ROA. BOPO has a negative and significant effect on ROA. NPF has a negative and significant effect on ROA. FDR has a positive and significant effect on ROA. While using size as a kontrol variable indicates that CAR has a positive and significant effect on ROA.